Hybrid GaAs (111)/GaAs (100) PIN photodiodes for metasurface-assisted nonlinear upconversion detection - Spedt, Vladimir; Meier, Falco; Geromel, René; Mahler, Pascal; Henksmeier, Tobias; Reuter, Dirk; Zentgraf, Thomas; Meier, Cedrik (Optics Express)
Efficient detection of near-infrared light at telecommunication wavelengths remains a central challenge for GaAs-based photonic and optoelectronic devices due to the absence of linear absorption below the bandgap. Here, we demonstrate a hybrid nonlinear optoelectronic device that enhances the detection efficiency of a (001)-oriented GaAs PIN photodiode under telecommunication-wavelength illumination, where absorption is intrinsically limited to two-photon absorption (2PA). Our approach relies on the integration of a transferred, nanopatterned 385 nm-thick (111)-oriented GaAs nanofilm acting as an on-chip nonlinear frequency-conversion layer. Elliptical GaAs nanoresonators are employed to enhance second-harmonic generation (SHG) resonantly, converting incident 1550 nm radiation into above-bandgap photons efficiently absorbed by the underlying diode. Spatially resolved current–voltage measurements reveal a pronounced enhancement of the detector response in regions covered by the nanoantennas. The device exhibits a low dark current, while the metasurface-covered regions show the largest current response under 1560 nm excitation compared to the bare GaAs(100) diode and the unstructured GaAs(111) film. These results establish a direct functional link between dielectric metasurface–based nonlinear frequency conversion and electrical photodetection, providing a viable route toward integrated sub-bandgap detection schemes.

Experimental determination of kinking angles with out-of-phase mixed-mode loading by means of a novel specimen geometry - Krome, Sven; Kullmer, Gunter; Weiß, Deborah; Duffe, Tobias; Ostwald, Richard (Discover Mechanical Engineering)
Abstract The service life of fatigue-loaded components that already contain manufacturing‑induced microcracks is primarily governed by the direction and the rate of fatigue-crack growth. When multiple loading components (e.g., tension, compression, shear) act simultaneously but not in temporal synchrony, out‑of‑phase mixed‑mode conditions occur. Such loadings are typical for automotive chassis parts and mechanically joined sheet‑metal assemblies. For optimized design of structural components, the crack kinking angle that occurs under mixed‑mode loading must be predicted as accurately as possible. At present, however, this is still challenging for out‑of‑phase loading conditions. To investigate the associated crack kinking behavior, a novel Compact‑Tension‑Shear‑Mini (CTSM) specimen was developed, enabling controlled generation of plane out-of-phase mixed-mode loading states. Experiments were performed under various combinations of cyclic and static mode I and mode II load components and compared with the analytical predictions of the Out-of-Phase Mixed-Mode (OMM) concept. The measured crack kinking angles showed very good agreement with the predicted values, with mean deviations of only a few degrees, demonstrating the validity and reproducibility of the approach. These findings confirm the applicability of the OMM concept for describing fatigue‑crack propagation under non‑proportional mixed‑mode loading and provide a basis for fatigue‑life assessment of clinched joints and other cyclic multi-axially loaded components.

Influence of the R-Ratio and the Temperature on the Coefficients of a Novel Exponential Approach for the Formulaic Description of Fatigue Crack Growth Rate Curves - Kullmer, Gunter; Krome, Sven; Weiß, Deborah; Schramm, Britta; Ostwald, Richard (Metals)
Investigating crack growth in sheet metal originating from clinched joints is a major part of predicting the service life of mechanically joined structures. Clinching allows different materials to be joined together. A key task in this context is to perform crack growth simulations in the vicinity of clinched joints considering different load and environmental conditions. This requires formulaic descriptions of the fatigue crack growth rate curves for the materials used. For this purpose, fatigue crack growth rate curves for different R-ratios and temperatures are determined experimentally. Generally, these fatigue crack growth rate curves can be described very well using a novel two-part exponential approach for the formulaic description of fatigue crack growth rate curves developed at Applied Mechanics of Paderborn University (FAM). In this case, three parameters are sufficient to describe the fatigue crack growth rate curves. For the material HCT590X, which is frequently used in clinched joints, it is shown as an example how the parameters vary with the R-ratio and the temperature. In addition, at high crack growth rates, a significant rise in the fatigue crack growth rate curve sometimes occurs at both low and high temperatures. To account for this feature, the two-part exponential approach can be expanded to include a third part.

Exploring Mathematics Teacher Noticing of Whole-Class Discussions Across Career Stages - Becker, Federica; Bruns, Julia (Proceedings of the 49th Conference of the International Group for the Psychology of Mathematics Education: Research Reports. PME.)
Research on teacher noticing highlights differences between novice and expert teachers, yet little is known about early career and intermediate expertise levels and how these expertise-related differences emerge in central teaching tasks and content areas. Facilitating whole-class discussions represents a central teaching task, such as when fostering flexible strategy use. This study examines expertise-related differences in mathematics teachers’ noticing in observed video scenes of whole-class discussions on flexible strategy use in Grade 1 using Epistemic Network Analysis. The preliminary results show no substantial differences between intermediate and expert teachers but between beginning teachers and the other two expertise groups regarding their noticing focus and the cognitive structures underlying their noticing processes.

Development and Modification of Porous Polymer Structures in the Vicinity of Cellulose Fibers - Pusse, S.; Heinz, S.; Limprasart, W.; Gemmer, L.; Witayakran, S.; Schabel, S.; Presser, V.; Gutmann, Torsten; Gallei, M. (Polymer Chemistry)

Multivariate counting of wild abelian extensions - Gundlach, Fabian (arXiv:2607.27364)
Let $K$ be a global function field of characteristic~$p$ and let $G$ be a finite abelian group of exponent $p^e$. We show that the multivariate generating function counting sub-$G$-extensions of $K$ with respect to $e$ specific height functions (encoding successive drops in the exponents of the higher ramification groups) is rational.

Klaus Fuchs-Kittowskis Radikaler Digitaler Humanismus: Ein kritischer Ansatz im Forschungsbereich Informatik und Gesellschaft. - Fuchs, Christian (Wissenschaft zwischen Krieg und Frieden – Verantwortung für eine menschwürdige Technik- und Gesellschaftsforschung)

Discourses on Discursive Machines. Review of Mark Coeckelbergh and David J. Gunkel, Communicative AI: A Critical Introduction to Large Language Models - Thomas, Sven (Jahrbuch Technikphilosophie)

Toni Loh: Feministische Technikphilosophie. Bielefeld: transcript 2025. 324 S. - Thomas, Sven (Zeitschrift für Didaktik der Philosophie und Ethik)

Harnessing tacit Knowledge from Sustainable Product Engineering through Artificial Intelligence - Mansheim, Johanna; Gräßler, Iris; Pfeifer, Jan Niklas (1st International Symposium: March 24 – 26, 2026, Heinz Nixdorf Institute, Paderborn University)
Tacit knowledge is particularly valuable in product engineering. Experiences reside in minds of employees and are not systematically documented but could have a significant influence on sustainable product engineering. Existing approaches do not offer sufficient support for harnessing technical tacit knowledge regarding sustainable product engineering. In this paper a three-step method is presented: The method contains knowledge acquisition, requirements extraction und requirements validation for quality assurance. Acquisition is performed by support artifacts like interview guidelines. Extraction is supported by Artificial Intelligence, converting statements into requirements. These requirements are validated using a specific questionnaire. The developed approach is applied in a funded project of the European Union (EU) with automotive industry partners. The method supports product engineers to collect tacit knowledge from experienced employees, transform unsystematic knowledge into standardized technical requirements and validate them. Application of this method enables creation of validated requirements that can be applied throughout the company and are not exclusively dependent on a single employee.
Keywords: Tacit knowledge; Sustainability; Product Engineering; Artificial Intelligence

Systematic review of engineering simulation models for life cycle assessment - Gräßler, Iris; Aydin, Simon; Rarbach, Sven (1st International Symposium: March 24 – 26, 2026, Heinz Nixdorf Institute, Paderborn University)
Manufacturing companies increasingly integrate the strive towards sustainability into product engineering to reduce resource consumption and environmental impacts. A substantial share of a product’s environmental performance is determined during engineering. Early assessments rely on generic data, which is gradually replaced by more concrete simulation and primary data as product maturity increases. The effective use of engineering simulation models for Life Cycle Assessment (LCA) therefore remains a central challenge under heterogeneous, distributed and rapidly evolving data. This article presents a systematic review of product engineering approaches for integrating simulation models into LCA. A seven-step research approach is applied to identify, categorize and evaluate existing approaches across CAx tools. Relevant simulation parameters for sustainability assessment, including material properties, process descriptors, consumables and waste streams, are identified and analyzed. Based on identified data characteristics, the potential of Data Science and Artificial Intelligence methods for LCA data preparation is assessed. A conceptual knowledge-graph-based decision support approach is derived to enable structured integration, traceability and reuse of simulation data for sustainability assessment. The approach is evaluated using criteria from literature. Structured integration of simulation data improves early-stage data quality and supports decision-making in sustainable product engineering.

Enabling extreme data by using DS/AI approaches - Gräßler, I.; Hesse, Thomas; Pottebaum, Jens (1st International Symposium on Hybrid Intelligence in Product and Production Engineering)
Design for Assembly, Disassembly and Reassembly (DfADR) prepares for high levels of material circularity in terms of repair and remanufacturing. The intention of reassembling products and their part simplies that inspection and sorting need to be integrated with value-conserving objectives. Further, disassembly and reassembly require higher competence levels of workforce than assembly. To provide the required information during engineering, a metadata model (MDM) is required that links established product models to capability models. Since processes to be carried out for realizing a product largely determine required employees’ capabilities, the proposed approach uses the ADR process domain to connect product and capability domains. The research is based on a systematic literature analysis to identify existing approaches regarding MDMs of ADR processes. Based on the results, an integrative MDM is developed that answers defined competence questions. The model enables queries which support engineers by feedback on which skills are required for a product. This builds up a basis to check whether required skills are available in the manufacturing company, either early in product engineering or later in ADR planning.

Perspectives on Privacy and Security in Collaborative AR - Insights from a Scoping Review and an Expert Interview Study - Krings, Sarah Claudia; Yigitbas, Enes; Sauer, Stefan (Blending Experiences in Interaction Design)
With a range of consumer devices available, augmented reality (AR) continues to make its way into everyday life and is also increasingly used in professional and sensitive contexts. Especially collaborative use cases, such as remote meetings or maintenance, offer potential, but also move issues in the area of privacy and security into focus. We conducted a scoping review to gain an overview of the current situation and found a lack of clear standards, with most approaches focusing on single protection features. Using the knowledge from the scoping review, we set up and conducted expert interviews. They revealed that end-users are almost completely dependent on developers or device manufacturers regarding their options for protection. The interviews also showed that most developers put little focus on privacy and security, often due to external constraints, such as employers treating the topic as an “afterthought” and not budgeting enough time for it. The experts suggested offering better software support to developers to enable the inclusion of privacy and security with less overhead as a solution. It was also suggested that a general rise in privacy and security awareness could improve the overall situation.

1st International Symposium : March 24 – 26, 2026, Heinz Nixdorf Institute, Paderborn University

SecCityVR: Visualization and Collaborative Exploration of Software Vulnerabilities in Virtual Reality - Wüppelmann, Dennis; Yigitbas, Enes (GI - Software Engineering)

What is Digital Democracy? - Fuchs, Christian (Journal of Information Technology & Politics)

The Words of Jesus and Scriptural Hermeneutics in the Qur’an - Ghaffar, Zishan (Islam and Christian–Muslim Relations)
This article examines the most frequently attributed statement of Jesus in the Qur’an, namely, ‘God is my Lord and your Lord’ (Q 19:36; Q 43:64; Q 3:51; Q 5:72; Q 5:117). It investigates the extent to which this formula is connected to Jesus’s words to Mary Magdalene on Easter morning in John 20:17. The analysis aims to show that the Qur’an critically engages with the Christian interpretive tradition surrounding this statement as recorded in John’s Gospel and adapts it – both contextually and verbally – within its own theological framework. As in the Christian tradition, this Qur’anic engagement also generates a broader discourse on the hermeneutics of scriptural interpretation.
Keywords: Qur’an; John 20:17; Scriptural hermeneutics; Words of Jesus; Intertextuality

Theoretical investigations of spatially multimode high-gain SU(1,1) interferometers - Scharwald, Dennis
In dieser Dissertation werden Aspekte von high-gain multimode SU(1,1) Interferometer theoretisch untersucht. Dabei wird der Prozess der parametrischen Fluoreszenz (PDC) mithilfe von Integro-Differentialgleichungen modelliert, welche die räumliche Entwicklung der Ebene-Wellen-Operatoren beschreiben. Es wurde gezeigt, dass Supersensitivität für die Phasenempfindlichkeit dieser Interferometer erreicht werden kann, sofern die Beugung der PDC Strahlung kompensiert wird. Weiterhin führt eine Erhöhung der parametrische Verstärkung und eine Reduktion der Schmidt-Zahl zu einer Verbesserung der Phasenempfindlichkeit und einer Verkleinerung des Phasenbereiches, über den die Supersensitivität erreicht werden kann. Basierend auf der Struktur der Schmidt-Moden von SU(1,1) Interferometern wurde ein numerisches Aufbereitungsverfahren konstruiert, welches die Messung der Stärke des Squeezing und Anti-Squeezing des Zustandes ermöglicht, der durch den ersten Kristall des Interferometers erzeugt wird. Das Verfahren wurde experimentell von Kooperationspartnern angewandt, wobei eine gute Übereinstimmung mit der Theorie festgestellt wurde. Zuletzt wurden SU(1,1) Interferometer mit Laguerre-Gauß-Moden als Pump-Strahlung für die Messung von Winkelverschiebungen untersucht. Es zeigte sich, dass sich die quantenmechanisch bedingte Messunsicherheit verbessert, wenn die parametrische Verstärkung oder die Indizes der Pump-Mode erhöht werden. Das generelle Verhalten gleicht dem der Phasensensitivität.

Metaphorische Konzeptualisierungen des Jahrhunderthochwassers in Süddeutschland im Spätfrühling 2024. Eine kognitiv-linguistische Analyse der überregionalen, online-journalistischen Berichterstattung - Dübbert, Alexander (Ökologische Diskurse heute. Inter- und transdisziplinäre Forschung zu globalen Herausforderungen und planetaren Grenzen)
Due to their devastating consequences, so-called century floods attract significant public attention and are therefore covered in nationwide media. In journalistic reporting, numerous conceptual metaphors are used to conceptualise such extreme weather events. This linguistic study investigates how the century flood that occurred in southern Germany in late May and early June 2024 was metaphorically conceptualised in nationwide online journalism by identifying patterns of metaphorical conceptualisation. The analysis draws on the foundations of Conceptual Metaphor Theory as proposed by Lakoff and Johnson (1980), refined through the graded distinction of schematicity levels in conceptual structure proposed in Kövecses (2017, 2020, 2022) Extended Conceptual Metaphor Theory. Accordingly, metaphors are understood as schematically distinguishable mappings of conceptual aspects from source to target areas, through which particular actions are constituted. Adopting a mixed-methods approach that integrates manual with (semi-)automatic analytical procedures, the study reveals that the century flood is predominantly conceptualised through the highly schematic metaphor ZEIT IST SUBSTANZ (›time is substance‹), the less schematic metaphor NATURKATASTROPHEN SIND PERSONEN (›natural disasters are persons‹), and a set of least schematic, elaborating metaphors, namely HOCHWASSER IST GEGNER (›flood is an opponent‹), HOCHWASSER IST ZERSTÖRER (›flood is a destroyer‹) and HOCHWASSER IST MÖRDER (›flood is a murderer‹). From an ecolinguistic perspective, the study critically reflects on how these metaphorical conceptualisations obscure human co-responsibility for the intensity of extreme flood events.
Keywords: Berichterstattung; Jahrhunderthochwasser; Kognitive Linguistik; konzeptuelle Metapher; Ökolinguistik; Schematizität

Intersection numbers for designs in regular semilattices - Kiermaier, Michael; Klawuhn, Lukas-André Dominik
We generalize intersection numbers for combinatorial designs to designs in finite meet-semilattices satisfying suitable regularity conditions. While designs in regular semilattices go back to Delsarte, our regularity assumptions are weaker than his and need not give rise to an association scheme. In this framework, we extend Mendelsohn's equations, prove a generalized Singleton bound with Steiner systems as equality cases, and determine the block intersection distribution at any block of a Steiner system. In particular, this distribution is independent of the chosen block. Specializing to several classical semilattice families, our results recover a number of well-known distributions in coding and design theory. In the Hamming and the $q$-Hamming (or bilinear forms) schemes, they give the local distance distributions of MDS and MRD codes, respectively. In the Johnson and $q$-Johnson (or Graßmann) schemes, they reproduce the block intersection distribution of classical and $q$-analog Steiner systems, equivalently the distance distribution of diameter-perfect constant-weight codes and diameter-perfect constant-dimension subspace codes. For the $q$-Johnson schemes, to the best of our knowledge, this result is new. As a further illustration, we apply our theory to designs of perfect matchings. Our approach provides a unified treatment of these cases in the strongest form known in the literature, determining the distribution relative to each individual block or codeword, without averaging and without linearity or additivity assumptions. Moreover, it identifies the natural double-counting objects underlying these distributions, leading to formulas in the regularity parameters of the semilattice and avoiding the more cumbersome expressions that arise in eigenvalue-based approaches via the ambient association scheme.